Journal Collection – Value for Money? - Eskelinen, Anu; Taskinen, Aino (Qualitative and Quantitative Methods in Libraries; Vol 3 No 1 (2014): March 2014 Issue, 2017)
In the past few years, Finnish universities have taken place within the major changes. Organizations have been merged and the new University Act came into effect on 1st January 2010. Under the new Act, the universities were given autonomy over decision-making, but also more responsibility for their own financing. At present, about 64% of the university budget is provided by the government and the rest of the financing comes from paid services, donations and sponsoring. The number of academic degrees and scientific publications is more and more important for university financing. Libraries have a significant role in supporting the publishing activities of the university by developing library services and acquiring resources for teaching and research. In our article, we want to make a short examination how much doctoral students of the University of Eastern Finland (UEF) have used journals acquired by the library for their dissertations and by this way give an example of how the UEF Library supports academic research by purchasing appropriate material. We also take notice to the acquirement of these journals. For the research material, we have chosen a few dissertations of each faculty of the University of Eastern Finland published during the year 2012.